Uji Daya Hambat Gel Semprot Ekstrak Daun Kersen (Mutingia Calabura L.) Terhadap Bakteri Staphylococcus Aureus Pada Pasien Penderita Luka Diabetes Melitus - Dhea Lovita Nasution; Astriani Natalia; Rena Meutia; Nerly Juli Pranita Simanjuntak (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Diabetes mellitus (DM) is caused by a metabolic disorder that affects the pancreas and is characterized by elevated blood sugar levels, also known as a metabolic disorder, which is caused by a decrease in the amount of insulin produced by the pancreas. Elevated blood sugar levels are also known as hyperglycemia. DM can potentially cause several complications, both macro- and microvascular. DM can cause cardiovascular disorders, which are serious and can be effectively managed if treated promptly, potentially leading to hypertension and heart attacks. Based on the above background, the researcher aims to study the effects of ethanol extract from Kersen leaves (Muntingia Calabura L.) on Staphylococcus aureus bacteria in diabetic patients with wounds, using varying concentrations of 1%, 1.25%, 1.5%, 1.75%, and 2%. Methods: The Kersen leaf extract was obtained through 96% ethanol maceration, then formulated into a spray gel using Carbopol 940 as a base. Stability evaluation included organoleptic testing, pH measurement, drying time, and spray pattern assessment. Antibacterial activity was tested using the disk diffusion method.Results: The spray gel demonstrated good physical stability over 21 days of storage. The antibacterial test yielded inhibition zones with diameters of 9.97 mm (1%), 16.01 mm (1.5%), 15.24 mm (1.75%), and 14.37 mm (2%), classified as moderate efficacy. The 1.5% concentration provided the highest inhibitory effect, although it was still below the positive control (clindamycin 1%). Conclusion: It has been demonstrated that the kersen leaf extract gel spray (Mutigia calabura L.) exhibits antibacterial activity in inhibiting the growth of S. Aureus bacteria, as evidenced by the formation of clear zones (inhibition zones) around the disk medium during testing. There is a direct correlation between the concentration of kersen leaf extract in the gel spray formulation and its antibacterial efficacy, with the highest efficacy at a concentration of 1.5%. This study provides a potential alternative for the treatment of diabetic wound infections using natural ingredients.